2022
DOI: 10.1155/2022/1222533
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin C on Gene Expression Profile of Inflammatory and Anti-Inflammatory Cytokines in the Male Partners of Couples with Recurrent Pregnancy Loss

Abstract: Immune system disorders and increased inflammation in the male reproductive system can lead to fetal risk in the early stages of development and implantation. Antioxidants such as vitamin C can play a protective role against sperm inflammatory reactions. This study aimed to evaluate the effect of vitamin C on the expression of inflammatory and anti-inflammatory cytokine genes in the male partners of couples with recurrent pregnancy loss. In this randomized clinical trial, twenty male partners of couples with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Altered sperm motility is crucial for male infertility [48], which is linked to asthenazoospermia as a major cause [49,50]. TNF-α has been indicated to cause a decrease in sperm motility due to its potential to induce increased generation of free radicals [5,42,43,51,52]. In this study, disomin demonstrated protective effect against DOX-induced sperm deficiency.…”
Section: Discussionmentioning
confidence: 72%
“…Altered sperm motility is crucial for male infertility [48], which is linked to asthenazoospermia as a major cause [49,50]. TNF-α has been indicated to cause a decrease in sperm motility due to its potential to induce increased generation of free radicals [5,42,43,51,52]. In this study, disomin demonstrated protective effect against DOX-induced sperm deficiency.…”
Section: Discussionmentioning
confidence: 72%
“…Both vitamins are able to reduce the inflammatory process by inhibiting the production of several proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin-1 (IL-1), IL-6, and monocyte-chemotactic protein-1 which may be responsible for responsible for the release of pain-inducing molecules [9,21,22]. This inhibition of the inflammatory process is also obtained through the activity of vitamin C and vitamin E which reduce the activity of the cyclooxygenase (COX) enzyme so that it will reduce the process of converting arachidonic acid into prostaglandin E2 (PGE2) which is responsible for modulating pain [9,23].…”
Section: Discussionmentioning
confidence: 99%
“…[18,44] These beneficial effects were primarily attributed to the antioxidant and testosterone booster properties of Vit-C that improve testicular performance. [10,17,40,44,45] Likewise, researchers reported a positive effect of Vit-C on sperm volume, motility, viability, morphology, and DNA integrity against arsenic-induced toxicity in animals and humans. [8,9,17,46] A recent cohort study also revealed positive relations between men's dietary intake of Vit-C and fertilization rate.…”
Section: Discussionmentioning
confidence: 99%